Identificação de subpopulações espermáticas por parâmetros morfométricos e fertilidade em sêmen bovino Bos taurus indicus - Santos, Ana Paula Castro (2016)
The aim of the present work was to identify and classify, by means of morphometry parameters of spermatozoa heads, different sperm subpopulations in frozen bovine semen, as well as the relation of the relative cell population in each subpopulation with in vitro fertilization. For this, samples of the semen of nine Bos taurus indicus (Nelore) animals were thawed, subsequently obtaining images of 200 cells per animal, considered as presenting normal morphology, which were treated with the software Image J. The variables used for determining the subpopulations were area, mass center and width. Semen samples of the same lot, regarding eight animals, were used for the in vitro fertilization of mature bovine oocytes, evaluating the pronuclear formation rate 20 hours after fertilization, as fertility rate evaluation. Four different subpopulations were identified, differentiated by the head of the spermatozoa (P<0.05), in order that the fourth subpopulation (SP4), characterized by cells with larger head area sperm, were majoritarian (42.7% of the cells). A negative correlation (r=-0.91; P<0.05) was verified between the relative proportion of cells in SP4 and the pronuclear formation rate. In conclusion, we suggest that the higher proportion of cells of larger head área sperm cells negatively interfere with in vitro fertilization.